CHANGES IN VALUES MEASURED WITH DIAGNOdent FOR ENAMEL AND DENTIN OF DECIDUOUS TEETH ETCHED FOR DIFFERENT TIME INTERVALS. - Vladimir E. Panov; Dobrinka M. Damyanova (Peytchinski Publishing, 2014)
Introduction: Dental caries continues to affect a large percentage of children and currently advises that if diagnosed at an early stage can be reversed with minimally invasive treatments. There a large number of methods for early diagnostics. Purpose: The aim of the presented in vitro study was to evaluate the effectiveness of the laser fluorescent device DIAGNOdent pen in measuring changes in the level of mineralization of intact deciduous teeth enamel surfaces etched for different intervals and of intact dentin etched for 30 seconds. Material and methods: The study was performed on extracted children teeth. DIAGNOdent was used to measure the values of laser fluorescence of intact enamel and dentinal surfaces. Samples were treated with 37% H2PO3 etched for 5 sec., 30 sec. and 60 sec. for enamel surfaces and 30 sec. for dentinal. Teeth were rinsed, dried and measured again with DIAGNOdent. Results: After etching the enamel surfaces for 5 sec., 30 sec. and 60 sec. an average increase of 1.55 (0.85-2.2) was detected. The detected average values of increase of laser fluorescence for the enamel were 0.85 for 5 sec. ethching; 1.6 for 30 sec. and 2.2 for 60 sec. The average increase in the dentine was 3.5. Conclusions: Based on the limitations of the conducted study it may be concluded that the changes in the degree of mineralization of deciduous tooth structures can be detected by DIAGNOdent. Enamel etching for 5 sec., 30 sec. and 60 sec. lead to a comparative degree of change in the laser fluorescence. The obtained values after 30 sec. of etching revealed almost a double increase compared to 5 sec. etching and 3-fold for those at the 60 sec. The measured changes after etching in the dentin were better expressed than those in the enamel.